The Analysis of Student Errors in Solving Flat Shape Problems - fatqurhohman, fatqurhohman; Disma, Elvira Hardyanti Lara; Kusumaningtyas, Yoga Dwi Windi (Department of Mathematics Education , University of Jember, 2023)
The purpose of this study is to describe the mistakes of class VII A students at SMP Negeri 2 Genteng, Banyuwangi Regency. This type of research uses descriptive qualitative. This type of research uses descriptive qualitative. Data collection techniques used written tests and semi-structured interviews. The subject of this research was class VII A students located at Genteng 2 Public Middle School. Subject data obtained 3 types of errors based on castor theory including conceptual errors, procedural errors, and technical errors. Conceptual errors include not writing formulas and symbols, writing formulas and symbols incorrectly. Procedural errors include, not writing down known, asked, or conclusions, wrongly writing down information known to the problem, unclear writing down the information asked, wrongly writing down the steps for solving the problem, not writing down the solution step at all. Technical errors include, not writing units in numbers that have units or answers, not writing units in the final answer, wrong writing units in numbers that should have units or answers, wrong writing units in the final answer, and wrong doing arithmetic operations